Realisasi Kompetensi Manajerial dalam Kepemimpinan Yang Efektif dan Visioner - Diana, Diana (ALACRITY : Journal of Education, 2024)
Managerial competence is closely related to effective and visionary leadership management because in fact management is essentially a matter of interaction between humans both vertically and horizontally, and is a very determining factor in the progress of an educational institution. Leadership can be said to be the behavior of motivating other people to work towards achieving certain goals through a long process that occurs slowly through observation and learning. This research aims to explain that the role of an effective and visionary leader must be balanced with commensurate managerial competence. This research uses a theoretical approach. The research results show that a leader in the world of education must have the ability to mobilize teachers, staff and employees, optimize school resources, have the capacity to guide students, and be able to set a good teaching example and then have a democratic style and be willing to accept suggestions and criticism from subordinates. and always communicate every policy and problem together.